2018
DOI: 10.1515/ntrev-2018-0067
|View full text |Cite
|
Sign up to set email alerts
|

Elemental zinc to zinc nanoparticles: is ZnO NPs crucial for life? Synthesis, toxicological, and environmental concerns

Abstract: The semi-conducting material zinc is one of the essential trace elements for humans, is a co-factor of more than 300 enzymes, and plays an important role in maintaining vital cellular functions. Deficiency of zinc may lead to cancer initiation; however, a high concentration also has toxic effects that might be life threatening. The toxicity can be addressed by the disequilibrium of zinc-mediated proteins and oxidative stress that produce nascent oxygen, hydroxyl radicals, and other reactive oxygen species. Zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
79
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(94 citation statements)
references
References 206 publications
0
79
0
2
Order By: Relevance
“…A study reported the antileishmanial activity of silver nanoparticles synthesized via Sargentodoxa cuneata by Ahmad et al, [ 27 ] as well as antileishmanial activity of ZnO nanoparticles synthesized via Linum usitatissimum L [ 28 ], comparing the activity of the bimetallic nanoparticles with monometallic nanoparticles. It is apparent that the activity of bimetallic is greater than monometallic, the higher the concentration of the nanoparticles the greater is the activity [ 29 ]. The synergistic effect of both metals (Zn and Ag) in for of nanoparticles or released ions has prognostic effect of antibacterial, antileishmanial and other biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…A study reported the antileishmanial activity of silver nanoparticles synthesized via Sargentodoxa cuneata by Ahmad et al, [ 27 ] as well as antileishmanial activity of ZnO nanoparticles synthesized via Linum usitatissimum L [ 28 ], comparing the activity of the bimetallic nanoparticles with monometallic nanoparticles. It is apparent that the activity of bimetallic is greater than monometallic, the higher the concentration of the nanoparticles the greater is the activity [ 29 ]. The synergistic effect of both metals (Zn and Ag) in for of nanoparticles or released ions has prognostic effect of antibacterial, antileishmanial and other biological activities.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the antibacterial activity of ZnO NPs was reported to be higher against the Gram-positive ( Staphylococcus aureus ) than the Gram-negative ( E. coli ) bacteria (Mirhosseini and Firouzabadi 2013 ). The difference in antibacterial activity is attributed to the particle size of the NPs, and their mechanism of antibacterial action is ascribed to damage of bacterial cell through the release of zinc (II) ions and generation of reactive oxygen species (Ali et al 2018b ; Gunalan et al 2012 ). Moreover, the presence of ZnO NPs reduces the effective pore sizes of the nanocomposite filters at little expense of energy consumption.…”
Section: Resultsmentioning
confidence: 99%
“…van der Waals forces and hydrogen bonds) composed of the aggregates of the sol particles [14,72]. Sol-gel process is utilised to synthesise various nano-inorganic materials or composite materials by the organic or inorganic materials of metal solution-gelation ("sol-gel") polymerisation process at low temperatures [73,74] and is considered as a highly flexible method for the synthesis of diverse range of materials, e.g. wide range of nano-/ micro-structures [75][76][77], and only requires mild conditions.…”
Section: Sol-gel Methodsmentioning
confidence: 99%